2011
DOI: 10.1297/cpe.20.33
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Diabetes Mellitus in Japanese Prader-Willi Syndrome

Abstract: Prader-Willi syndrome (PWS) is frequently associated with marked obesity and diabetes mellitus (DM). Although the overall frequency of DM in PWS ranges from 7–20%, there is only limited data available on Japanese patients. This study evaluated five factors associated with DM in PWS: 1) frequency, 2) age of onset, 3) risk factors, 4) long-term complications and 5) treatment. Sixty-five patients, ranging in age from 10 to 53 yr, were studied retrospectively. The frequency of DM in patients over 10 yr of age was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
23
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 20 publications
4
23
1
Order By: Relevance
“…The prevalence of T2DM in the present study was 13.7% (29/211). This proportion is similar to that of previous studies (7–25%) [ 13 16 ]. Considering the prevalence of T2DM in adults (6.1–6.9%) [ 17 ] and 0.2% in children younger than 18 years in Korea [ 18 ], the prevalence rate of T2DM in Korean PWS is sufficiently high to warrant attention.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The prevalence of T2DM in the present study was 13.7% (29/211). This proportion is similar to that of previous studies (7–25%) [ 13 16 ]. Considering the prevalence of T2DM in adults (6.1–6.9%) [ 17 ] and 0.2% in children younger than 18 years in Korea [ 18 ], the prevalence rate of T2DM in Korean PWS is sufficiently high to warrant attention.…”
Section: Discussionsupporting
confidence: 92%
“…A recent Italian cohort study revealed a 13.5% prevalence of T2DM, which was similar to our results [ 15 ]. This proportion is relatively lower than the results of a Japanese study, which were 26.2% [ 16 ], but higher than in a French study, 0% [ 19 ]. The differences in the described frequencies of T2DM have presumably resulted from various sizes of the PWS base population, the diagnostic approach to T2DM, the wide range of the age group, and the study period.…”
Section: Discussioncontrasting
confidence: 74%
See 1 more Smart Citation
“…GH may decrease insulin sensitivity, whereas the improvement of body composition by GH treatment may lower the risk of DM. Tsuchiya et al (3) reported that the frequency of DM in PWS was 9.7% among the patients treated with GH, while 41.2% in the patient who did not receive GH treatment developed to DM. Among the Korean patients with PWS, 72.4% in the DM group and 90.9% in the non-DM group had a history of GH treatment (10).…”
Section: Discussionmentioning
confidence: 99%
“…PWS patients become overweight in early childhood due to an insatiable appetite and, therefore, onset of DM is generally during adolescence at the earliest [ 3 ]. Prevalence of DM was reported 22% in 68 patients older than 13 years (age of youngest person with DM) in United Kingdom [ 3 ], whereas 26.2% in 65 Japanese patients older than 10 years (age of youngest person with DM) [ 4 ]. The type of DM was mostly non-insulin dependent in both cohorts [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%